Conscious sedation in dentistry: Effectiveness of two medications in children - Ascanio Llaja, Karina del Rosario (2009)
The midazolam technique has been used in pediatric patients with fear or anxiety to obtain relaxation and to modify negative conduct. The objective of this study was to evaluate if hydroxyzine, an antihistaminic depressor of the central nervous system, added to midazolam technique by oral dosage provides more suitable levels of sedation. 24 children between 2 to 6 years of age, ASA I, with negative conduct (Frankl scale II) were distributed and randomized in two groups; the first group (I) received midazolam 0,75 mg/kg of weight; and the second group (II) received midazolam 0,75 mg/kg of weight plus hydroxyzine 1 mg/kg of weight. It was observed sedation level in the scale of Houpt, and vital signs were checked throughout the treatment. The results showed that: in group I, 58,3% obtained very good to excellent, sedation levels, 33,3% good to regular sedation levels and 8,3% poor sedation level. In the other group, 91,7% obtained very good to excellent sedation levels, 8,3% good to regular sedation levels and 0% poor sedation levels (p =0,01). The vital signs values didn’t show differences between the groups and were within normal clinical parameters. No adverse effects of relevance were observed in any of the cases. It was concluded that Combined Conscious Sedation Technique showed to be superior in effectiveness, showing significant statistically advantages in patient movement and in total evaluation of sedation parameters. It was also effective to provide better sedative effects and to be well tolerated by pediatric patients, being able to be used as an effective alternative for the control of negative conducts during the dental treatment.